Post-harvest operations and physicochemical and sensory quality of coffees - Clemente, Aline Consolação Sampaio; Cirillo, Marcelo Angelo; Malta, Marcelo Ribeiro; Caixeta, Franciele; Pereira, Cristiane Carvalho; Rosa, Sttela Dellyzete Veiga Franco (Coffee Science - ISSN 1984-3909, 2015)
The effects of post-harvest processing and drying operations and storage conditions are relevant factors for consideration in assessing coffee quality. In this respect, depending on the processing and drying conditions, coffee beans may undergo changes in their physicochemical composition, with a direct affect on beverage quality and, consequently, sensory assessment. Univariate statistical techniques are usually used for analysis of the results, but such results may lead to inconsistent interpretations because they do not consider the combined effect of physicochemical and sensory variables. Therefore, the aim of this study is to propose a multivariate approach to the data by a combination of principal component techniques and Multi-Vari Charts which consider the physicochemical and sensory variables together with the post-harvest operations in the assessment of coffee beans quality. Fruit from Coffea arabica L. ‘Catuaí Amarelo IAC 62’ were processed to obtain natural coffee, semi-washed coffee and fully-washed coffee. After processing, the coffees were dried in the shade, in the sun and in mechanical dryers and were kept for twelve months in cold storage at 10ºC and 50% RH, with assessment every four months. We conclude that the use of principal component analysis in conjunction with the graphical technique multivari- chart enables us to understand the combined effects of processing, drying and storage on the chemical and sensory quality of the coffee, as well as their correlations. Observe greater reductions in the final score and conductivity during storage in natural coffees dried in a dryer.